2019
DOI: 10.3390/ijms20143552
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Insulin Resistance in Heart Failure: The Role of Mitochondrial Dynamics

Abstract: Heart failure (HF) frequently coexists with conditions associated with glucose insufficiency, such as insulin resistance and type 2 diabetes mellitus (T2DM), and patients with T2DM have a significantly high incidence of HF. These two closely related diseases cannot be separated on the basis of their treatment. Some antidiabetic drugs failed to improve cardiac outcomes in T2DM patients, despite lowering glucose levels sufficiently. This may be, at least in part, due to a lack of understanding of cardiac insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 80 publications
1
22
0
3
Order By: Relevance
“…In fact, glucose metabolism and fatty acid metabolism in the heart are strictly controlled by insulin signal. Impaired insulin signal or insulin resistance play a decisive role in the occurrence and development of HF 96 . Therefore, the correction of insulin resistance and the elimination of insulin signal-mediated interference factors in patients with HF are of positive significance to prevent heart disease and improve the prognosis of patients with HF.…”
Section: Related Pathways and Targets Of Energy Metabolismmentioning
confidence: 99%
“…In fact, glucose metabolism and fatty acid metabolism in the heart are strictly controlled by insulin signal. Impaired insulin signal or insulin resistance play a decisive role in the occurrence and development of HF 96 . Therefore, the correction of insulin resistance and the elimination of insulin signal-mediated interference factors in patients with HF are of positive significance to prevent heart disease and improve the prognosis of patients with HF.…”
Section: Related Pathways and Targets Of Energy Metabolismmentioning
confidence: 99%
“…Past studies have established that hunger or reduced insulin signals are a strong trigger for autophagy ( 92 , 184 , 185 ). Hyperglycemia can induce myocardial mitochondria division but inhibit mitophagy, causing the accumulation of functionally impaired mitochondria ( 57 , 186 , 187 ). Additionally, DRP1 and ROS have mutually reinforcing associations ( 188 ).…”
Section: The Pathophysiological State Of Mitochondrial Dynamics and Mitophagymentioning
confidence: 99%
“…Alteration of energetic substrate utilization in myocardium and modification of its intra-cellular signaling pathway also play important roles for the pathogenesis and progression of HF [81]. Previous animal studies revealed that the dietary n-3 PUFA intake altered the mitochondrial membrane phospholipid composition in cardiomyocytes, which led to a decrease in myocardial oxygen consumption without loss of ventricular power generation [82,83].…”
Section: Evidence Of the N-3 Pufa-mediated Cardiac Protection Frommentioning
confidence: 99%